Rediscovery of Social Reality of the City and the Village: Methodological Novations of the Study of Life Space Dynamics - C. I. Ildarhanova (Vestnik MGIMO-Universiteta)
The world sociological thought pays more attention to the dynamics of urban-rural relations within the modernization of the living space. Their achievements are highlighted in the paper. Social problems of rural society that is changing and is being changed under the influence of development of network relations with the city are suggested to be analyzed in the context of living space of a new quality that is forming in the modern world. Sociological vision of the concept is presented on the base of international urban-rural theoretical constructs, explaining formation of a new establishing space by specifics of social capital, influence of living environment on space configuration, and historical retrospective of rural society institualization under the conditions of globalization and development of network relations. The difference between concepts 'living environment' and 'living space' is explained in the broader context of the second one. Unlike subjects it includes actors with their various ties like internet, new types of mobility of people, goods and capitals towards the city that go far and far outside local of inhabiting and are not restricted just by subjective world of place of inhabiting. Social space localization in definite living environment, according to the author's viewpoint, possesses important social and cultural value. Living space analysis is structured by differentiation of social groups based on social and cultural causality. The author brings value and cultural basis of changes in social actions of citizens of a modern village and traces the role of social and cultural environment on development of network processes in a rural territory. It is underlined how demographic resources of a rural society lead to the lost of relations that are formed on a community type rather than on a society type. Processes of urbanization of a rural area and rurbanization of the society are given in an axiological perspective. Three dimensions of sustainability of urban-rural relations are described: including economic, social and environmental spheres. The author supposes that evaluation of social capital of each of spatial communities study of social norms, values and behavioral standards will promote prognosis of the potential of modern rural-urban space as a base for institualization of new urban-rural relations. Attention has been drawn to the necessity to develop new urban-rural dichotomy and oppose not rural/urban spaces but areas, both urban and rural, that change and are being changed under the influence of introspection.